Mastitis Accompanied by Lymphadenitis in a Dog Caused by Staphylococcus hyicus - Araújo, Marina R.; Preis, Ingred S.; França, Sílvia A.; Paniago, Juliana G.; Costa, Mirella C.; Oliveira, Juliana S. V.; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2011)
Canine mastitis is an infrequent condition that occurs most commonly in the postpartum period due to ascending bacterial infection. This report aims to describe clinical, pathological and bacteriological aspects of mastitis caused by Staphylococcus hyicus accompanied by disseminated superficial lymphadenitis in a dog. In the postpartum period the animal showed clinical signs of prostration, dyspneia, and unresponsivess to environment. At physical examination, hypothermia, dehydration and subcutaneous edema of the limbs were detected. Gross and histologic features were consistent with marked purulent and necro-hemorrhagic mastitis accompanied by lymphangitis, lymphadenitis and thromboembolic pneumonia. Isolation and biochemical identification confirmed the infection by Staphylococcus hyicus. This study shows that one must be attentive not only of the risk of uterine infection postpartum, but also of the possibility of mammary gland infection.